Ecotourism site in relation to tourist attitude and further behavioural changes - Cheng, Mingming; Jin, X.; Wong, I. (Routledge, 2014)
Despite the emergence of ecotourism in both practice and academic literature in China during recent decades, relatively little is known about the role of ecotourism site, especially in relation to tourist attitude and further behavioural change. This article seeks to address the deficit on the role of ecotourism site in Chinese domestic tourist attitude change and further adaptation of sustainable behaviour. Using a qualitative research approach with 28 interviews, the authors show that Chinese domestic tourists have become more environmentally conscious after visiting ecotourism sites and further reveals the influence of the perceived health benefits, and the ecological value of unity of nature and human beings on Chinese domestic tourists attitude change. The findings offer important implications for both tourism practitioners and academics.